The study of the stress-strain state of trunk gas pipeline sections with defects in the shape of the cross-section of the pipe - К.А. Poliarush, Yu.І. Doroshenko Ya.V. Doroshenko, L.D. Pylypiv (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
There is carried out 3D modeling of the trunk gas pipeline sections with defects in the cross section shape of the pipe - dents and ovalities. The ANSYS Fluent R18.0 Academic software packge simulates gas flow through these sections of the gas pipeline. The mathematical model of the gas motion is based on the solution of the Navier–Stokes equations and the energy transfer, closed by a two-parametric model of the Launder–Sharma turbulence, using a wall function with corresponding initial and boundary conditions. The structure of the gas flow in the sections of the gas pipeline with defects of the cross section shape of the pipe is investigated. The simulation results were visualized by designing flow lines, the fields of velocity and pressure modules on the contours, in longitudinal and cross-sectional sections. The exact values of velocity and pressure at different points of the inner cavity of gas pipeline sections with defects in the cross-section shape were determined. The places of slowdown and acceleration of gas flow, increase and decrease of pressure were found.